Differentiation of oral candidal species based on the internally transcribed spacer (ITS) regions of rDNA / Raja Ahmad Zahir Raja Halinuddin - Raja Halinuddin, Raja Ahmad Zahir (2012)
Candida is a genus of opportunistic yeast that are usually harmless residents of the oral cavity, but they become pathogenic under conditions which allow them to increase their proportion to other members of the oral microflora. Correct and accurate identification of the candidal species infecting an oral candidiasis patient is important due to antifungal drug resistences. The region in the fungal genome that contains the gene that codes for rRNA, also known as rDNA, has been found to be useful for phylogenetic studies and species identification. The purpose of this study is to compare the candidal loads of denture wearers, periodontal disease patients, and a control group, in addition to differentiating isolated oral Candida sp. based on rDNA, in order to assess the effectiveness of using the rDNA region for candidal species identification. Samples from the saliva and the surfaces of the palate, tongue and cheek mucosa were collected from 45 individuals consisting of three target groups: periodontal disease patients, denture wearers with healthy oral cavity, and non-denture wearers with healthy oral cavity as the control group. The samples were subjected to serial dilution and spread on agar plates, which were then scored for Colony-Forming Units (CFUs). Next, fifteen random candidal colonies were isolated and subjected to genomic DNA extraction based on glass beads disruption. ITS1, ITS2, ITS3 and ITS4 primers were used to amplify regions in the rDNA, and the ITSI-5.8S-ITSII region was then digested by HinfI and MspI restriction enzymes. The microbial loads on all the sites of denture wearers groups was found to be significantly higher than the control group, while only the microbial loads on the tongue surface of the periodontal disease group was significantly higher than in the control group, while at all the other sites there was no significant difference. Comparing the restriction fragment lengths of the clinical samples to that of seven ATCC control species allowed the identification of Candida albicans, Candida tropicalis, Candida parapsilosis, Candida dubliniensis and Candida glabrata (C. krusei and C. lusitaniae were also among the iii ATCC control species and could be differentiated, but none of the clinical samples were of those species). One clinical sample had a unique band and restriction fragment pattern that could not be matched to any of the control species, however based on the band sizes it is most likely to be Candida famata. The MspI restriction digest was not able to distinguish between C. albicans and C. dubliniensis, whereas the HinfI digest could not distinguish between C. tropicalis and C. parapsilosis. In conclusion, candidal colonization in denture wearers, while there appears to be no significant difference in periodontal patients other than on the tongue surface. Furthermore, restriction enzyme digestion of the candidal rDNA region is potentially useful for candidal species identification.